2020
DOI: 10.1038/s41437-020-0325-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of multiple sex-chromosomes associated with dynamic genome reshuffling in Leptidea wood-white butterflies

Abstract: Sex-chromosome systems tend to be highly conserved and knowledge about their evolution typically comes from macroevolutionary inference. Rapidly evolving complex sex-chromosome systems represent a rare opportunity to study the mechanisms of sex-chromosome evolution at unprecedented resolution. Three cryptic species of wood-white butterflies-Leptidea juvernica, L. sinapis and L. reali-have each a unique set of multiple sex-chromosomes with 3-4 W and 3-4 Z chromosomes. Using a transcriptome-based microarray for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 76 publications
7
46
2
Order By: Relevance
“…This result is consistent with similar findings in K. inachus ( Yang et al 2020 ), Danaus plexippus ( Mongue et al 2017 ), and Spodoptera exigua ( Zhang et al 2019 ), which all possess a W chromosome that lacks sequence homology to the Z or autosomes. To our knowledge, cytogenic and PCR-based studies have only shown clear homology between derived or neosex chromosomes, and never to putatively ancestral sex chromosomes in Lepidoptera (e.g., Yoshido et al 2020 ).…”
Section: Resultsmentioning
confidence: 92%
“…This result is consistent with similar findings in K. inachus ( Yang et al 2020 ), Danaus plexippus ( Mongue et al 2017 ), and Spodoptera exigua ( Zhang et al 2019 ), which all possess a W chromosome that lacks sequence homology to the Z or autosomes. To our knowledge, cytogenic and PCR-based studies have only shown clear homology between derived or neosex chromosomes, and never to putatively ancestral sex chromosomes in Lepidoptera (e.g., Yoshido et al 2020 ).…”
Section: Resultsmentioning
confidence: 92%
“…Although transposable elements can be dispersed on many chromosomes or even throughout the entire genome, large amplification of the elements are often found on sex chromosomes in many organisms ( Ahmad et al, 2020 ; Koomgun et al, 2020 ; Laopichienpong et al, 2020 ; Yoshido et al, 2020 ). The presence of accumulated TEs leads to the establishment of heterochromatin, and possibly also to TE recombination between non-homologous copies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that early differentiation of multiple sex chromosomes in Drosophila miranda was accompanied by the massive amplification of gene copies leading to their tandemly repeated arrangement on both X and Y chromosomes [ 112 ]. Similarly, the amplification of genes linked to complex multiple sex chromosome systems was observed also in wood white butterflies of the genus Leptidea [ 113 ], suggesting that the mechanism could be a common feature of sex chromosome differentiation. Thus, a combination of gene amplification with the frequent sex chromosome turnover observed in fishes, both possibly induced by increasing mutation load, could systematically create novel selectable variation and thus considerably increase the adaptive potential in fishes (cf.…”
Section: Evolutionary Pathways Of Teleost Multiple Sex Chromosomes: Current State Of Knowledge and Further Research Directionsmentioning
confidence: 99%